Macroeconomics versus 'Common Sense' - Kazimierz Laski (The Vienna Institute for International Economic Studies (wiiw), 2004)
The very basis of macroeconomics is the circular flow of expenditures and incomes. From this follows the conclusion that it is demand which determines supply and not vice versa. The most paradoxical result of this approach is the hypothesis that investment finances itself by quantity adjustment, if capacity and labour are not fully employed (a typical feature of a capitalist economy) or by price adjustment, i.e. by demand-pull inflation (if capacity and labour force are underemployed).
Keywords: E1; E2; P5; 330; consumer goods surplus; income and capacity effect of investment; quantity versus price adjustment; two-sector model